Effects of Research Requirements on Mental Health and Academic Performance of Ph.D Scholars - Dr. A. Sivagami; T. Sugasini (South Eastern European Journal of Public Health, 2025)
This study explores the impact of mandatory research publication requirements on the stress levels of Ph.D. scholars in Tamil Nadu, with a focus on how these pressures affect their mental health, academic performance, and overall well-being. The research was conducted in Thanjavur District, Tamil Nadu, where 120 Ph.D. scholars from various disciplines, including social sciences, humanities, and natural sciences, were surveyed. The main objective was to assess the extent of stress caused by publication requirements, identify the factors contributing to this stress, and evaluate the impact on scholars' mental health and academic outcomes. The study employed a quantitative, descriptive research design using a cross-sectional survey method. A self-designed online questionnaire was used as the primary tool for data collection, featuring a stress measurement scale, questions on publication frequency, and demographic information. Random sampling was utilized to ensure a representative sample of the target population, which included a diverse range of scholars in terms of age, gender, academic discipline, and employment status. The study reveals that a significant majority (58.3%) of Ph.D. scholars experience high levels of stress due to publication pressures, with 60% identifying publication requirements as a major stressor. Mental health issues, including anxiety and burnout, were prevalent among 65% of respondents, indicating a strong correlation between publication stress and negative psychological outcomes. The study also found that stress adversely affects academic performance, with 58% of scholars reporting that their research quality and productivity suffer as a result. Academic institutions may implement mentorship programs, offer workshops on stress management and academic skills, and enhance access to mental health resources to better support scholars. By addressing these issues, the academic environment can be made more supportive, enabling scholars to thrive both personally and professionally.